'The continuation of sovereign capture by other means': biopolitical tattooing and the shared logic of the exception and securitisation. Issue 1 (2nd January 2019) - Murphy, Michael P. A.
ABSTRACT: Carl Schmitt's description of the sovereign decision has played an important role in works of securitization theory and biopolitical approaches to security studies. While analysis of the securitization of an isolated referent object may be clearly different from the analysis of a generalized state of exception as in the concentration camp, both processes tend toward the same end. When securitization is iterative rather than isolated, it creeps across society and could potentially move all political activity into the realm of security. This problem of "securitization creep" highlights the danger of analyzing security in isolation or in limited iterations. By turning to Giorgio Agamben's paradigm of biopolitical tattooing, this article analyzes the danger of securitization creep and its relation to the state of exception. While sometimes regarded as a pessimistic thinker, Agamben's affirmation of the agency of the citizenry in his call to reject biopolitical tattooing also bears resemblance to the ability of the audience to reject a securitizing move. Not only are securitization and biopolitics in the state of exception related historiographically to the work of Schmitt, but also in the capacity of the citizenry to ameliorate political futures by rejecting sovereign overreach.